El desarrollo de los actos del habla a través de la interacción del trabajo en grupo entre los estudiantes de noveno año a en el colegio de bachillerato 27 de febrero de la ciudad de Loja durante el año escolar 2016-2017 - Cordero Olmedo, Selena Jackeline (2018)
The purpose of this research work was to develop the speech acts of English among students of the ninth year A at Colegio de Bachillerato 27 de Febrero through group work interaction. For the development of the present work, the following methods were applied: scientific, analytical-synthetic, descriptive and statistical. The intervention plan was developed in eight sessions. The instruments used to collect the data were: observation sheets, class notes, tests and questionnaires. The results obtained from the posttest revealed the progress of students in the use of speech acts. The answers received from the questionnaires showed a remarkable change of attitude in the students when working in groups. Based on these results, it is concluded that the change in students was meaningful, and their scores on the development of speech acts increased significantly